Una fraterna amistad: : Ricardo Palma y Luis Benjamín Cisneros - Pérez Garay, Carlos Alberto (2018)
The present work tries to show the great friendship that existed between these two writers, linked to the Peruvian Romantic Movement. Friendship that by the way, occurred in different areas of life.